Cohort profile: The Bristol IVF Study- A longitudinal study of women, their partners and treatment outcomes following assisted reproductive technologies - Amy E. Taylor; Taemi Kawahara; Jennifer Provis; Karema Al Rashid; Sophie Fitzgibbon; Alix Groom; Amanda Jefferys; Paul Wilson; Scott M. Nelson; Valentine Akande; Deborah A. Lawlor (PLoS ONE, 2026)
Background The Bristol IVF Study (BRIST-IVF) is a longitudinal clinical cohort, established to determine factors related to successful live birth and other outcomes following conception by assisted reproductive technologies (ART). This cohort profile describes recruitment, data collection and planned research. Methods The study gathered comprehensive sociodemographic, lifestyle, anthropometric, and clinical data from women and their partners before and during treatment, as well as during pregnancy and after birth. Biological samples, including blood, urine, and saliva, were collected at initial recruitment and at pregnancy clinics, with cord blood and placental tissue obtained at birth. Participants consented to NHS record linkage, allowing access to pregnancy and birth outcomes from obstetric notes. Data collection during pregnancy and after birth followed the same protocols as a naturally conceived cohort, the second generation of the Avon Longitudinal Study of Parents and Children (ALSPAC-G2). Results Between 3rd September 2019 and 30th June 2023, 502 couples or single women were recruited (967 individuals in total). Of these, 490 women underwent 1,055 ART treatment cycles during the study follow-up (up to 31st March 2024). Recruited women had a mean age of 35.8 years (SD = 4.4) and a mean BMI of 25.1 (SD = 4.4). At the time of recruitment, 251 women (50%) had never been pregnant, and 374 (75%) had not had a previous live birth. Women and their partners with a confirmed viable pregnancy at a scan performed at 7 weeks of gestation were invited to participate in the pregnancy follow-up study, with 305 women (for 324 pregnancies) invited. Data were collected from pregnancy questionnaires (n = 246, 76%), pregnancy clinic data (n = 119, 37%), and birth questionnaires (n = 223, 69%). Collection of obstetric data from health records is ongoing. Conclusion The BRIST-IVF cohort enables novel research into the predictors and consequences of ART conception, with comparison to ALSPAC-G2.